2015
DOI: 10.1093/brain/awu399
|View full text |Cite
|
Sign up to set email alerts
|

Gait training facilitates central drive to ankle dorsiflexors in children with cerebral palsy

Abstract: Foot drop and toe walking are frequent concerns in children with cerebral palsy. The main underlying cause of these problems is early damage and lack of maturation of the corticospinal tract. In the present study we investigated whether 4 weeks of daily treadmill training with an incline may facilitate corticospinal transmission and improve the control of the ankle joint in children with cerebral palsy. Sixteen children with cerebral palsy (Gross Motor Classification System I:6, II:6, III:4) aged 5-14 years ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 63 publications
(103 reference statements)
3
55
0
1
Order By: Relevance
“…Chief among these are changes in the neural drive to the muscles and improved coordination of the muscle activity during gait. [13] Recently evidence of increased corticospinal drive to the tibialis anterior muscle following gait training has been provided, and it is likely that similar changes may contribute to the observed improvement in gait ability in our subjects. The complexity of gait requires a multifactorial analysis in order to reveal the significance of each of the possible contributing factors.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Chief among these are changes in the neural drive to the muscles and improved coordination of the muscle activity during gait. [13] Recently evidence of increased corticospinal drive to the tibialis anterior muscle following gait training has been provided, and it is likely that similar changes may contribute to the observed improvement in gait ability in our subjects. The complexity of gait requires a multifactorial analysis in order to reveal the significance of each of the possible contributing factors.…”
Section: Discussionmentioning
confidence: 72%
“…[11,12] Prior to this age, the gait pattern appears to be flexible and may also in children with CP be changed relatively easily through training. [13,14] This appears to relate to plastic changes in the central drive to the muscles and thus suggests that the central mechanisms involved in controlling gait are not so rigid despite the brain lesion that they cannot be trained. There is however also evidence that such plastic changes are less easy to induce in children older than 10 years.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same drive that elicits EEG-EMG synchrony can also lead to task-dependent synchronous activation among paired EMG recordings, such as synergistic muscles (as in the present study) or between different regions of a single muscle [Baker, Olivier, 1997, Grosse, Cassidy, 2002, Kilner, Baker, 1999, Neto, Baweja, 2010]. A number of prior studies have shown that central nervous system disease and functional deficits are linked to reduced EMG synchrony in gamma/Piper bands [Petersen et al, 2013, Willerslev-Olsen et al, 2015]. However, in the present study there was no significant group difference in EMG Piper synchrony during typical walking.…”
Section: Discussionmentioning
confidence: 75%